ANALISIS TERHADAP POLA PENILAIAN HASIL BELAJAR PESERTA DIDIK PADA MATERI SEGIEMPAT MELALUI MODEL PEMBELAJARAN KOOPERATIF - Acep Tanto; Usep Kosasih; Sidiq Aulia Rahman (UJMES (Uninus Journal of Mathematics Education and Science), 2020)
This research study is motivated by assessments in study groups that tended to be an individual assessment to each student, which resulted to the lack of students’ motivation to teach their friends in the groups who do not understand the material, so the discussion process in learning is less effective. The purpose of this research study is to observe the pattern of effective assessment on the cooperative model learning in terms of student learning outcomes. The method used in this research is a qualitative descriptive method with a type of reflection research. The reflection is used to get feedback on the lessons learned, including: 1) Lesson reports 2) Surveys and questionnaires, 3) Audio and video recordings, 4) Observation. Data collection is done by tests, interviews, documentation and observations. The results of the study of previous studies obtained four models of assessment patterns; low levels students assessment pattern, medium levels students assessment pattern, group average assessment pattern, and individual assessment pattern. Based on the results of the analysis, this research study concludes that the effective assessment pattern in achieving learning objectives in cooperative learning is with the group average assessment model.